Evaluating the Impact of Worldwide Market Crises on Indonesia’s Financial Sector: A Comparative Examination of the Global Financial Crisis (GFC) and COVID-19 Pandemic - Mohamad Ikhsan Modjo; Clara Calista Hidayat; Gatot Soepriyanto (SAGE Open)
The study examines how the 2007 to 2008 Global Financial Crisis (GFC) and the recent COVID-19 pandemic have affected the risk-return profile of the Indonesian financial sector index (IDXFinance). Using weekly return data from 2005 to 2022 and the GARCH-M model, the analysis evaluates volatility persistence and clustering. The study employs two dummy variables to represent the two crisis situations, and daily and monthly data analyses are used to validate the findings. The research reveals that the GFC crisis had a negative impact on stock returns, causing volatility clustering and increased IDXFinance return volatility. On the other hand, the COVID-19 pandemic had a less centralized influence on stock returns and volatility. The COVID-19 pandemic had a more subdued impact than the GFC, which began in and affected the banking sector. This study is among the first to examine the response of Indonesia’s financial sector to two market crises, and it provides investors with insights into how financial crises like the GFC and COVID-19 affect the Financial Sector Index in Indonesia’s return and volatility. The study also highlights the risk and financial sector performance, which can be helpful for policymakers and practitioners to anticipate and mitigate future risks.